Tìm x :
\(\left(\dfrac{x-3}{x-2}\right)^3-\left(x-3\right)^3=16\)
Các bạn giải giùm mik nha
Tìm x :
\(\left(\dfrac{x-3}{x-2}\right)^3-\left(x-3\right)^3=16\)
Các bạn giải giùm mik nha
Tìm x :
\(\left(\dfrac{x-3}{x-2}\right)^3-\left(x-3\right)^3=16\)
Các bạn giải giúp mik nha
Giải PT: \(\left(\dfrac{x-3}{x-2}\right)^3-\left(x-3\right)^3=16\)
Giải hệ pt;
\(\left\{{}\begin{matrix}xy\left(x+y\right)=x^2-xy+y^2\\\dfrac{1}{x^3}+\dfrac{1}{y^3}=16\end{matrix}\right.\)
Giải phương trình:
1, \(\left(x^2+x+1\right)\left(x^4+2x^3+7x^2+26x+37\right)=5\left(x+3\right)^3\)
2, \(\left(x+1\right)^3+\left(x+3\right)^3+6\left(x+1\right)\left(x+7\right)\left(x+3\right)=8\left(x+2\right)^3\)
3, \(x^3+\left(x-1\right)^3+3x\left(x-1\right)\left(x^4+x\right)=\left(2x-1\right)^3\)
4, \(\dfrac{\left(x+1\right)^3}{3x+1}+\dfrac{x^3+5x+2}{x^3+2x+1}=x+3\)
5, \(\dfrac{5x^3+x^2+x+1}{4x^2+1}+\dfrac{6\left(4x^2+1\right)}{x^3+x^2+1}=x+7\)
6, \(\left(x^2-4x+1\right)^3+\left(8x-x^2+4\right)^3+\left(x-5\right)^3=125x^3\)
Giải phương trình \(\dfrac{3\left(x-\sqrt{3}\right)\left(x-\sqrt{5}\right)}{\left(1-\sqrt{3}\right)\left(1-\sqrt{5}\right)}+\dfrac{4\left(x-1\right)\left(x-\sqrt{5}\right)}{\left(\sqrt{3}-1\right)\left(\sqrt{3}-\sqrt{5}\right)}+\dfrac{5\left(x-1\right)\left(x-\sqrt{3}\right)}{\left(\sqrt{5}-1\right)\left(\sqrt{5}-\sqrt{3}\right)}=3x-2\)
Cho x,y,z>0 /xyz=8.
Tìm min P= \(\dfrac{x^2}{\sqrt{\left(1+x^3\right)\left(1+y^3\right)}}+\dfrac{y^2}{\sqrt{\left(1+y^3\right)\left(1+z^3\right)}}+\dfrac{z^2}{\sqrt{\left(1+z^3\right)\left(1+x^3\right)}}\)
Giải phương trình:
1, \(\left(x+3\right)\left(3x^4+8x^2+12x+21\right)=5\left(x^2+1\right)^3\)
2, \(3\left(x^2+2x-1\right)^2-2\left(x^2+3x-1\right)^2+5x^2=0\)
3, \(\dfrac{x^2+x+1}{x+1}+\dfrac{x^2+2x+2}{x+2}-\dfrac{x^2+3x+3}{x+3}-\dfrac{x^2+4x+4}{x+4}=0\)
4, \(\left(\dfrac{x+6}{x-6}\right)\left(\dfrac{x+4}{x-4}\right)^2+\left(\dfrac{x-6}{x+6}\right)\left(\dfrac{x+9}{x-9}\right)^2=2.\dfrac{x^2+36}{x^2-36}\)